Droning on. (Economist, 2010)
The article profiles the Ethical Architecture software created by Dr. Ronald Arkin of the Georgia Institute of Technology's School of Interactive Computing, which would be used to operate a drone in the decision to attack in warfare. The software's ability to upgrade information about the destruction caused by the drone is explored. The systems that the drone would be programmed with and the ability for it's decisions to be overridden are discussed.